IMPACT OF TIMELY ANTIBIOTIC THERAPY ON OUTCOMES OF NEONATAL SEPSIS - Bahronova Dilshoda Tohirovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Neonatal sepsis is a major cause of morbidity and mortality in newborns, particularly in preterm and low-birth-weight infants. Prompt initiation of empiric antibiotic therapy is critical to improving outcomes, reducing complications, and lowering mortality rates. This study examines the impact of timely antibiotic administration on the clinical outcomes of neonates with sepsis. Findings indicate that early initiation of appropriate antibiotics significantly reduces the risk of severe complications, shortens hospital stays, and improves survival. Delays in therapy are associated with increased mortality and poor clinical outcomes, emphasizing the importance of rapid recognition and immediate intervention in neonatal sepsis management.